Polymer‐Functionalized Mitochondrial Transplantation to Plaque Macrophages as a Therapeutic Strategy Targeting Atherosclerosis. Issue 5 (25th March 2022) - Liu, Haoran; Wu, Suhong; Lee, Hyunho; Baudo, Gherardo; Massaro, Matteo; Zhang, Aijun; Hamilton, Dale J.; Blanco, Elvin
Abstract: The pro‐inflammatory microenvironment that contributes to atherosclerotic plaque progression is sustained by M1 macrophages. Metabolic reprogramming toward heightened glycolysis accompanies M1 macrophage polarization, with approaches aimed at lessening glycolytic metabolism in macrophages standing to impact disease progression. The objective is to decrease the inflammatory response in atherosclerotic lesions by inducing favorable metabolic phenotypes in macrophages using an innovative mitochondrial transplantation strategy. The hypothesis is that delivery of mitochondria, functionalized with a dextran and triphenylphosphonium (Dextran‐TPP) polymer conjugate for enhanced cellular transplantation, to atherosclerotic plaques properly regulates M1 macrophage bioenergetics, attenuating inflammatory processes and preventing plaque progression. Dextran‐TPP mitochondria transplantation to M1 macrophages has profound effects on cell bioenergetics, resulting in increased oxygen consumption rate and reduced glycolytic flux that coincides with a decreased inflammatory response. Upon intravenous delivery to ApoE −/− mice fed a high fat diet, Dextran‐TPP mitochondria accumulate in aortic plaques and co‐localize with macrophages. Importantly, Dextran‐TPP mitochondria treatment reduces the plaque burden in ApoE −/− mice, improving cholesterol levels, and ameliorating hepatic steatosis and inflammation. Findings highlight Dextran‐TPP mitochondria as a novel biological particle for the treatment of atherosclerosis, underlining the potential for macrophage metabolic regulation as a therapy in other diseases. Abstract : M1 macrophages drive atherosclerotic plaque progression. The pro‐inflammatory phenotype of M1 macrophages is associated with glycolytic reprogramming. Herein, transplantation of polymer‐functionalized mitochondria decreased glycolytic metabolism in M1 macrophages, lessening their inflammatory response. Moreover, polymer‐functionalized mitochondria reduced plaque burden and liver damage in a murine atherosclerosis model. Findings highlight the potential of targeting diseases whose hallmark includes aberrant macrophage bioenergetics.